(untitled) (Praxis Educativa, 2014)
English teacher training courses have been generally rooted in a positivist paradigm. Because of an epistemological turn, this paradigm is changing looking for local answers appropriate for the sociopolitical and economic contexts where the prospective teachers are bound to teach. This change implies confronting myths such as the advantages of being a native speaker of the language and creating teachers as transformative intellectuals in their working environments. This paper proposes the use of narratives as a pedagogical tool and at the same time as a methodology of analysis in order to arouse voices of teachers and students searching for that new identity.